The supercritical pile model of GRB: tapping the proton energy and getting the νFν peak at ∼1 MeV - Kazanas, Demosthenes; Georganopoulos, Markos; Mastichiadis, Apostolos (2004)
We propose a process by which the kinetic energy of the protons, that carry most of the energy of GRB relativistic blast waves (RBW), is converted explosively into relativistic electrons of the same Lorentz factor, which then produce the observed prompt γ-ray emission of the burst. This conversion is the result of the combined effects of the reflection of photons produced within the flow by upstream located matter, their re-interception and conversion into e +e --pairs on the RBW by the pγ→ pe +e - reaction. This process depends on kinematic and dynamic thresholds; the former depends on the RBW Lorentz factor Γ while the second on the column density of the post shock matter to the pγ→e +e - reaction; this latter condition is in effect that of the criticality of a nuclear pile, hence the erminology. It is shown that, when operating near threshold, the resulting GRB spectrum produces its peak luminosity at energy (in the lab frame) E≃ mec2, thereby providing an answer to this outstanding question of GRBs.
Keywords: galaxies: active; quasars: general; Radiation Mechanisms: Nonthermal; X-rays: galaxies